9. The Holistic Approach to Music Education Throughout the Life Course: News and Perspectives - Cosumov Marina (Sciendo, 2023)
Music, constituting a great phenomenon of the world, represents an inherent element in the daily life of society, in the consciousness and nature of man, because everything is movement, everything is vibration, everything is sound. The relationship "man-music (arts)" places in the foreground the educational function through which it - educates moral feelings, human qualities, cultivates the spiritual sphere of man. Musical education throughout life is presented as a continuous individual process of spiritual self-improvement of the personality through multiple forms of relationship with the art of music. In this context, musical education is significant to perpetuity - lifelong education, on the three dimensions of the human being: biological, intellectual, spiritual, because it is implicitly based on the undulating character of the universe, the cosmos and human existence.